Analysis of understanding by design concept of teachers’ independence and creativity in developing evaluations of mathematics learning in inclusion schools - Sumandya, I Wayan; Widana, I Wayan; Suryawan, I Putu Pasek; Handayani, I Gusti Agung; Mukminin, Amirul (Edelweiss Applied Science and Technology, 2023)
Independence and creativity in developing evaluations of mathemetics learning based on the comprehension of the Understanding by Design (UbD) concept are skills that mathematics teachers in inclusive schools must possess. This research aimed to obtain an accurate and comprehensive picture of teacher independence and creativity in developing evaluations of mathematics learning based on understanding the concept of Understanding by Design (UbD). It used mixed methods by design, which combined quantitative and qualitative approaches. The population was all mathematics teachers in inclusive schools in the provinces of Bali, Nusa Tenggara Barat (NTB), and Nusa Tenggara Timur (NTT). The sample selection used the cluster random sampling technique, with a total sample of 465 math teachers. Furthermore, the data were collected using a questionnaire. The results of the group mean difference test on teacher independence in developing evaluations of learning mathematics in inclusive schools were obtained at 11500.249, and on teacher creativity in developing learning mathematics evaluations in inclusive schools, they were obtained at 13129.593. It showed that understanding the concept of Understanding by Design (UbD) influences teacher independence and creativity in developing evaluations of learning mathematics in inclusive schools. Increasing the independence and creativity of teachers in the provinces of Bali, NTB, and NTT to develop Understanding by Design (UbD)-based learning evaluations can be done by preparing guidelines for developing Understanding by Design (UbD)-based learning evaluations that can be utilized by teachers studying independently.